Combined searches for the production of supersymmetric top quark partners in proton–proton collisions at √s=13Te - KAYA, MİTHAT (My University, 2021)
© 2021, The Author(s).A combination of searches for top squark pair production using proton–proton collision data at a center-of-mass energy of 13Te at the CERN LHC, corresponding to an integrated luminosity of 137fb-1 collected by the CMS experiment, is presented. Signatures with at least 2 jets and large missing transverse momentum are categorized into events with 0, 1, or 2 leptons. New results for regions of parameter space where the kinematical properties of top squark pair production and top quark pair production are very similar are presented. Depending on the model, the combined result excludes a top squark mass up to 1325Ge for a massless neutralino, and a neutralino mass up to 700Ge for a top squark mass of 1150Ge. Top squarks with masses from 145 to 295Ge, for neutralino masses from 0 to 100Ge, with a mass difference between the top squark and the neutralino in a window of 30Ge around the mass of the top quark, are excluded for the first time with CMS data. The results of theses searches are also interpreted in an alternative signal model of dark matter production via a spin-0 mediator in association with a top quark pair. Upper limits are set on the cross section for mediator particle masses of up to 420Ge.
Keywords: Fizik; Astronomi ve Astrofizik; Temel Bilimler; Mühendislik ve Teknoloji; Physics; Astronomy and Astrophysics; Natural Sciences; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Temel Bilimler (SCI); Mühendislik; Uzay bilimi; ASTRONOMİ VE ASTROFİZİK; Engineering, Computing & Technology (ENG); Natural Sciences (SCI); ENGINEERING; SPACE SCIENCE; ASTRONOMY & ASTROPHYSICS; Mühendislik (çeşitli); Fizik Bilimleri; Fizik ve Astronomi (çeşitli); Engineering (miscellaneous); Physical Sciences; Physics and Astronomy (miscellaneous)